PENGARUH CAMPURAN BIOETANOL DESTILASI MOLASE TEBU DENGAN PERTALITE TERHADAP PERFORMA, KONSUMSI BAHAN BAKAR, DAN EMISI GAS BUANG MOTOR BENSIN 125cc - Andhikatama, Alpha Bagas; Rahardjo, Winarno Dwi (Automotive Science and Education Journal, 2020)
The purpose of this research is to determine the value of torque, power, fuel consumption and exhaustemissions on a 125cc 4-stroke gasoline engine by providing treatment for the fuel used. The treatmentused is in the form of mixing bioethanol fuel with alcohol content of 99.63% with pertalite 90 fuel on amixture variation of 0%, 5%, 10%, 15%, 20%, 25%, 30%. The gasoline motor used in this study was theHonda Vario 125 Esp which was tested in the engine speed range of 3000, 3500, 4000, 4500, 5000, 5500,6000, 6500, 7000, 7500, and 8000 rpm using the Dynamometer, Exausht Gas Analzer and burette Thereare 2 highest torque values in the tested fuel namely 25% bioethanol fuel mixture with 75% pertalite witha torque value of 22.56 Nm at 4000 rpm and 30% bioethanol fuel mixture with 70% pertalite with a torquevalue of 22.56 Nm at 3500 rpm, the highest power value in the tested fuel is 30% bioethanol fuel mixturewith 70% pertalite with power value of 9.62 kW at 4500 rpm, the lowest fuel consumption value in 30%bioethanol fuel mixture with 70% pertalite % with FC value of 0.134 kg / h, while the lowest Hydrocarbon(HC) value in the tested fuel is 30% bioethanol fuel mixture with 70% pertalite achieving i 743.67 ppm.The addition of bioethanol is not accompanied by a decrease in Carbon Monoxide (CO) gas levels. Thereis the lowest Carbon Monoxide (CO) value in the tested fuel, that is pure pertalite fuel itself, which is1.14% vol.Keywords: Bioethanol, Pertalite, Torque, Power, Fuel Consumption, Flue Gas Emissions Dynamometer, Exhaust Gas Analyzer, Carbon Monoxide, Hydrocarbon.